Prolactin Induced Protein (PIP) is a potential biomarker for early stage and malignant breast cancer. (June 2018) - Gangadharan, Anju; Nyirenda, Themba; Patel, Kishan; Jaimes-Delgadillo, Nydia; Coletta, Dominique; Tanaka, Takemi; Walland, Ayal C.; Jameel, Zena; Vedantam, Srinivasa; Tang, Sittinon; Mannion, Ciaran; Lee, Grace Y.; et al.
Abstract: Objectives: Breast cancer (BC) is the second leading cause of cancer-related mortality in women. Bioinformatic analysis and expression screening showed that Prolactin Induced Protein (PIP) was differentially expressed in BC. The objective of this investigation was to characterize the expression pattern of PIP, an aspartyl proteinase, in malignant and non-malignant breast tissues. Materials and Methods: Real time quantitative PCR was employed to analyze PIP and androgen receptor ( AR ) mRNA levels in BC cell lines and 190 normal tissues and tumor samples. The tumor specimens were categorized based on TNM classification, anatomic stage, histologic grade and molecular subtype and expression pattern evaluated. To detect protein levels, immunohistochemistry followed by semi quantitative scoring was employed in the examination of 517 normal, benign, and invasive BC tissues. Results: We observed substantial downregulation of PIP transcription in cancer samples compared to normal breast tissue. mRNA levels were significantly downregulated (93 fold, P < 0.005) in advanced grades compared to lower grades. Transcript levels were also significantly lower (22 fold, P < 0.05) in triple negative tumors compared to hormone receptor positive tumors. Significant downregulation was observed in early stage samples of triple negative and hormone receptor positive tumors. Though PIP protein showed a wide range of expression levels in BC, early stage samples showed significant downregulation. Conclusions: PIP mRNA is significantly downregulated in early stage BC compared to normal breast tissue. Consequently, low PIP mRNA expression in BC tissues could potentially be used as a tissue based biomarker to assist pathologists in confirmation of early stage BC diagnosis. Highlights: PIP transcription is downregulated in high grades and stages of breast cancer (BC). Early stage triple negative BC samples showed lowest median gene expression values. PIP protein is also downregulated in early stage invasive breast tumors.